Numerical investigations on the methane-oxygen diffusion flame-street phenomena in a microchannel: Effects of wall temperatures, inflow rates and global equivalence ratios on flame behaviors and combustion performances. (15th September 2020) - Sun, Bowen; Kang, Xin; Wang, Yu
Abstract: "Flame-street" is an exotic diffusion flame behavior characterized by the peculiar formation of intermittent reaction-zones in the mixing layer of fuel and oxidizer streams in a micro-channel. In the present work, parametric studies were numerically performed to investigate the influences of operation conditions on flame behaviors as well as the overall performances of the micro-burner. The operation conditions investigated included wall temperatures (500–1400 K), methane/oxygen inflow rates (5/10–650/1300 sccm) and global equivalence ratios (0.5–2.0). The number of flame segments was observed to show a non-monotonic variation trend (first increasing from one to three and then decreasing from three to one) as the wall temperature or total inflow rate increased; while it was noticed to be insensitive to the variation of global equivalence ratios. The combustion efficiency and the ratio of heat loss to heat release were found to increase and decrease, respectively, with the increase of the wall temperature, except during the process when reductions of flame numbers occured. Above the very low-inflow rate regime, both the combustion efficiency and heat loss-to-release ratio increased as the inflow rate increased, unless a reduction of flame numbers took place (which can result in significant drops in both parameters). As the global equivalence ratio increased, the combustion efficiency decreased monotonically while the heat loss-to-release ratio stayed at a relatively constant level. Highlights: Effects of operation conditions on CH4 –O2 micro-diffusion flame behavior were parametrically studied. Wall temperature and inflow rate had significant impacts onflamecharacteristics. Discrete flame-street phenomena were observed for a moderate level of wall temperatures and inflow rates. Global equivalence had limited effect on the flame-street structure. Combustor overall performances were evaluated among all studied operation conditions.